Ruthenium modulated Ni-Co pyrophosphate architectures enabling accelerated oxygen evolution in anion exchange membrane electrolyzer - Kim, Su-hyeon; D Rodney, John; Deepapriya, S.; Kim, Ga-hwa; Junita, J.; Kale, Amol Marotrao; Velayutham, Rajavel; Devasena, T.; John, Josfel Flora; Jung, Keeyoung; Raj, C. Justin; Kaya, Cengiz; et al. (ELSEVIER, 2026)
The development of efficient and durable electrocatalysts remains crucial for sustainable production of hydrogen via water electrolysis. Herein, we report a ruthenium-modified nickel-cobalt pyrophosphate [(NiCo)(P2O7)] catalyst (Ru-NCP) as a class leading oxygen evolution electrode under alkaline conditions and its application in anion exchange membrane water electrolysis (AEMWE). The NiCo2O4 precursor was transformed into a pyrophosphate framework through phosphidation, followed by Ru deposition and thermal reduction under Ar/H2. Structural analyses (XRD, Raman, TEM, XPS) confirmed the formation of the (NiCo)(P2O7) lattice and Ruinduced modulation of metal oxidation states. Electrochemical studies revealed an overpotential of 1.567 V at 100 mA cm- 2 and stable operation at 400 mA cm- 2 for 24 h in 1.0 M KOH. Integrated into an AEMWE, Ru-NCP achieved 1.6 A cm-2 at 4.5 V with extended durability. The superior performance arises from Ru-mediated electronic reconfiguration and enhanced active site accessibility within the pyrophosphate matrix.
Keywords: Ruthenium; Nickel-cobalt pyrophosphate; Oxygen evolution reaction; AEM water electrolysis; HIGH-ENERGY DENSITY; COPPER-OXIDE; LANTHANUM SUBSTITUTION; BIFUNCTIONAL ELECTRODE; STRUCTURAL-PROPERTIES; WATER; ELECTROCATALYSTS; PARAMETERS; NANOWIRES; OXIDATION; Science & Technology - Other Topics; Materials Science